Environmental constraints in selecting urban trees: landscape architect’ views / Ramly Hasan, Noriah Othman and Faridah Ismail. - Hasan, Ramly; Othman, Noriah; Ismail, Faridah (Universiti Teknologi MARA Cawangan Selangor, 2019)
This research explored the environmental constraints based on landscape architect’s views in selecting urban trees. Two objectives have been formulated (i) to examine the practice in selecting tree species among landscape architects and (ii) to determine the relationship between practice and environmental constraints in selecting urban tree species. The findings showed that specific criteria of the environmental constraints are positively correlated and have a strong relationship with tree selection practice. The views of the landscape architect are pertinent in tree selection practice. The findings of this research will contribute to practise improvement in selecting urban tree species by landscape architects in the future.